Swarm, Evolutionary, and Memetic Computing Third International Conference, SEMCCO 2012, Bhubaneswar, India, December 20-22, 2012. Proceedings - Panigrahi, Bijaya Ketan; Das, Swagatam; Suganthan, Ponnuthurai Nagaratnam; Nanda, Pradipta Kumar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Third International Conference on Swarm, Evolutionary, and Memetic Computing, SEMCCO 2012, held in Bhubaneswar, India, in December 2012. The 96 revised full papers presented were carefully reviewed and selected from 310 initial submissions. The papers cover a wide range of topics in swarm, evolutionary, memetic and other intelligent computing algorithms and their real world applications in problems selected from diverse domains of science and engineering.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Artificial intelligence; Optical pattern recognition; Computer Science; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Pattern Recognition; Computer Communication Networks; Software Engineering